"Dei Verbum": Scripture, Tradition, and Historical Criticism - Thiel, John E. (Horizons, 2020)
The Council Fathers at Vatican II struggled to negotiate the Council's teaching on divine revelation with regard to the teaching of Trent, but more immediately with regard to the modern theology of the Magisterium and the modern value of historical criticism that had recently been recognized by Pius XII as having a legitimate role in the interpretation of Scripture. Dei Verbum's teaching stressed the unity of Scripture and tradition in the revelation of God's word, but never considered the role of historical criticism in the interpretation of God's word in tradition that it affirmed in God's revelation in the biblical word. This article argues that the recognition of the legitimate role of historical criticism in the interpretation of tradition remains an issue of needed development in the teaching of Dei Verbum.